Dynamic cosine-Gauss plasmonic beam through phase control - Xiao, Kai (2014)
We carry out an approach to dynamic manipulation of a nondiffracting cosine-Gauss plasmonic beam (CGPB) illuminated with an incident phase modulation within nanostructures by a spatial light modulator (SLM). By changing the hologram addressed on the SLM, dynamic control on the lobe width and the propagating direction of the CGPB is experimentally verified. Finally, we demonstrate an application example of this dynamic CGPB in routing optical signals to multichannel subwavelength wave guides through numerical simulation.